FRI0278 Risk factors for mortality in patients with lupus nephritis: a long-term study at a single center in japan. (23rd January 2014) - Kayakabe, K.; Ikeuchi, H.; Hiromura, K.; Kadiombo, A. T.; Sakurai, N.; Sakairi, T.; Kaneko, Y.; Maeshima, A.; Nojima, Y.
Abstract : Background: Lupus nephritis (LN) is a major cause of morbidity and mortality in patients with systemic lupus erythematous (SLE). Previous reports showed age (>50 years), nonwhite race, and renal dysfunction at the time renal biopsy are life-threating factors 1, 2 ) . However, there are few studies focused on Asian patients with LN. Objectives: We performed a retrospective analysis to investigate mortality and its risk factors in LN patients at our institution. Methods: One hundred fifty-eight patients (21 male and 137 female; 154 Japanese, 2 Chinese, 1 Pilipino and 1 Thai) who received renal biopsy and diagnosed with LN at our institution from 1975 to 2012 were examined. Results: The mean observation period after renal biopsy was 9.8±7.6 years. The mean patient age, estimated glomerular filtration rate (eGFR) and urinary protein at the time of renal biopsy were 36.2±13.4 years, 79.2±33.1 ml/min/1.73m 2 and 3.97±4.08 g/gCr, respectively. Renal histology by ISN/RPS 2003 classification was as follows; II 12.7%, III 14.6%, IV 41.8%, V 14.5%, III/IV+V 14.5%. Steroids were used in all patients and immunosuppressants were added to 122 patients (77.2%). During the observation period, progression of renal dysfunction defined by doubling serum creatinin or end-stage kidney disease (ESRD) were observed in 14 patients (8.9%) and in 9 patients (5.7%), respectively. Eighteen patients were died; infection (n=4), cardiovascular diseases (n=4), malignancy (n=3), intestinal perforation (n=2), CNS lupus (n=1), gastrointestinal hemorrhage (n=1), pulmonary hemorrhage (n=1), traffic accident (n=1) and suicide (n=1). The average period between renal biopsy and death was 11.9±8.6 years. Early death within 1 year was observed only in 2 patients. Five, 10 and 20-year survival rates were 95.5, 93.1 and 76.1%. Statistical significant risk factors for increased mortality by univariate analysis were as following; age (>50 years), positive for anti-SSB antibody, complication of CNS lupus, overlap with other autoimmune diseases, complication with diabetes mellitus and progression of kidney dysfunction. Neither eGFR at the time of renal biopsy nor ISN/RPS class was associated with mortality. A multivariate stepwise Cox hazard model revealed the following 3 parameters as the independent risk factors for death; age (>50 years) [Hazard Ratio (HR) 9.0, 95%CI 2.6 to 31.5, p=0.001], complication with CNS lupus [HR 20.1, 95%CI 4.0 to 99.7, p<0.001] and progression of renal dysfunction [HR 5.2, 95%CI 1.6-17.0 p=0.007]. Conclusions: From data of our single-center cohort of LN patients in Japan, age (>50 years) at the time of renal biopsy, complication with CNS lupus and progression of kidney dysfunction were found as independent risk factors for increased mortality. Although early death was rare, infection, cardiovascular diseases and malignancies were major causes of death during long-term follow-up of LN. References: Austin III HA. Nephrol Dial Transplant. 1995;10:1620-8. Korbet SM. J Am Soc Nephrol. 2007;18:244-54. Disclosure of Interest : None Declared